CEFR-aligned language tests: A systematic scoping review - Wan Abdul Halim, Wan Alisa Hanis; Nik Mohd Alwi, Nik Aloesnita (Elsevier Ltd, 2022)
The Common European Framework of Research (CEFR) is not geared to be a standard for test development. Even so, the framework is used as a reference in many language tests, resulting in these tests being identified as CEFR-aligned language tests. To date, there is an increasing number of CEFR-aligned language tests. Several studies have been conducted to determine the purposes of CEFR-aligned language tests and the relevance of CEFR in CEFR-aligned language tests, particularly writing tests. Therefore, the current paper conducted a systematic scoping review (SRR) on CEFR-aligned language tests with a focus on writing tests. A total of 31 papers from 2011 to 2021, sourced from ScienceDirect, were reviewed. The current SRR was guided by the Systematic Evidence-Based Approach (SEBA), with minor modifications. The current study discovered that the CEFR-aligned language tests served five purposes, with each type of test adopted different conditions of testing procedure and judging criteria. Despite that there is a limited clear correlation between the purpose of language tests and the condition of the testing procedure and judging criteria, the current SRR confirms the need for rater training in CEFR-aligned language tests, even when raters present a solid grasp of the CEFR.